Expelling excellence: Exchange visitor restrictions on high-skill migrants in the United States - Michael A. Clemens; Jeremy Neufeld; Amy M. Nice (Institute of Labor Economics (IZA), 2024)
We examine a little-known restriction on high-skill immigration to the United States, the Exchange Visitor Skills List. This List mandates that to become eligible for long-term status in the U.S., certain high-skill visitors must reside in their home countries for two years after participation in the Exchange Visitor Program on a J-1 visa. While well-intended to prevent draining developing nations of needed skills, today the Skills List in practice is outdated and misdirected. It is outdated because it fails to reflect modern economic research on the complex effects of skilled migration on overseas development. It is misdirected because, as we show, the stringency of the List bears an erratic and even counterproductive relationship to the development level of the targeted countries. The List is also opaque: there have been no public estimates of exactly how many high-skill visitors are subject to the list. We provide the first such estimates. Over the last decade, an average of between 35,000 and 44,000 high-skill visitors per year have been covered by the home residency requirement via the Skills List. Despite the stated purpose of the List, these restrictions fall more heavily on relatively advanced economies than on the poorest countries. We describe how a proposed revision to the List can address all three of these concerns, balancing the national interest with evidence-based support for overseas development.
Keywords: F22; J24; O15; O33; 330; migration; skill; human capital; talent; restrictions; barriers; visa; policy; brain drain; brain gain; development; migration; immigration; innovation; research; science